(untitled) (The Pakistan Development Review, 2002)
The objective of this paper is to examine how economists have perceived the contributions of agriculture to the economic development process and then to present the case for the critical role that research, extension, and information can play in agricultural productivity growth and thus in economic development, particularly in low income countries. After a brief presentation of the framework commonly used to examine productivity growth, a distinction is made between technological change and technical efficiency. This distinction is crucial for policy purposes because the major impetus behind technological change are research and development, while education and experience are critical to improving managerial capabilities to make efficient use of a given technology. Empirical findings concerning the returns on agricultural research, with special attention to studies that have focused on Pakistan, are discussed. The paper then offers an overview of alternative methodologies available to measure technical efficiency, summarises the empirical literature, and finally focuses on studies dealing with Pakistani agriculture. Once it is established that improvements in technical efficiency could contribute significantly to increases in farm output and income, the discussion moves to some issues that have implications for the measurement and potential improvement of farm efficiency. An overview of a model of privatised extension services, currently being applied in some Latin American countries and which could have some relevance to conditions in Pakistan and elsewhere, is provided. The paper ends with the contention that significant improvements are needed in the collection and organisation of farm production data if we are to advance our understanding of the drivers of productivity growth at the farm level.